KESESUAIAN ANTARA MANIFESTASI KLINIS DENGAN LOKASI MENINGIOMA ORBITOKRANIAL JINAK - , IDA AYU NARAYANI, dr. Agus Supartoto, Sp.M(K) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background : Clinical manifestations of meningioma are dependent on many factors, including its location. Recognizing the specific clinical manifestations for various tumour location will help physicians in early diagnose of meningioma. Objective : This study was conducted to confirm to which degree there is a relation between the clinical manifestations of benign orbitocranial meningioma and its tumour location. Methods : The researcher employed retrospective study with qualitative descriptive method. Samples were medical records and CT imaging interpretation taken from the Laboratory of Anatomi Pathology and Medical Record Instalation of Dr. Sardjito Hospital during 2011-2012. Collected data will be grouped and analysed in a qualitative descriptive manner and conclusion will be drawn based on previous journals that discussed simillar subject. Result : In this research, 4 cases were reported as convexity meningioma in which patients complained for headache (4 cases), visual loss (2 cases), papil atrophy (3 cases), and pupil dilatation (3 cases). 1 case was reported as retrobulbar meningioma. Headache, exopthalmos, and visual loss were confirmed in this patient. 4 cases were reported as sphenoid wing meningioma and headache (4 cases), visual loss (2 cases), exopthalmos (4 cases), papil atrophy (1 case), high intraocular pressure (1 case) were confirmed. Conclusion : In this research, it was concluded that the tumour location of benign orbitocranial meningioma did not always relate to its clinical manifestations. In the case of retrobulbar meningioma, there was a strong relation, while in convexity and sphenoid meningioma, such relation was less evident.